ESTIMATION OF GROUNDWATER USING THE RESISTIVITY GEOELECTRIC METHOD OF WENNER SCHLUMBERGER CONFIGURATION IN PLALANGAN VILLAGE, KALISAT SUBDISTRICT, JEMBER - Sa'diah, Aminatus; Anggraeni, Firdha Kusuma Ayu; Yushardi, Yushardi (Jurnal Fisika dan Aplikasinya, 2024)
Water is a source of basic needs that is needed by all living things including humans. Palalangan Village, Kalisat Subdistrict is one of the areas that often experiences drought during the dry season, resulting in a water crisis that will hamper the daily activities of the population. The purpose of this study is to determine the subsurface lithological structure based on rock resistivity values and groundwater potential using the resistivity geoelectric method in Palalangan Village, Kalisat District. The research was conducted experimentally in the field using the wenner-schlumberger configuration resistivity geoelectric method to obtain primary data in the form of field measurement data and collect relevant literature studies to obtain secondary data. The results showed that from the first pass to the fifth pass consisted of groundwater material, sandstone, claystone, passive silt soil, gravel, sand, and dry gravel. The potential for groundwater with a considerable amount is found in track 5 which is thought to contain groundwater material with a resistivity value of 6 05 Ωm - 25.7 Ωm at a depth of 1m to 13.8m. This can be seen from the density of the blue color produced through data interpretation